2019
DOI: 10.1039/c9cc02969a
|View full text |Cite
|
Sign up to set email alerts
|

The π-acidity/basicity of cyclic trinuclear units (CTUs): from a theoretical perspective to potential applications

Abstract: Au(i)/Ag(i)/Cu(i) cyclic trinuclear units display highly adjustable π-acidity/basicity and relevant multiple superior potential applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
82
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(83 citation statements)
references
References 93 publications
1
82
0
Order By: Relevance
“…Thus, it can be concluded that 10-20-nm shift of the absorption wavelength was induced by dimer formation. The calculation results for the DT6 dimer, which have previously been reported, suggested that the electronic transitions in the excitation spectrum can be assigned to a transition from the ligand-based π-orbital to intermolecular non-covalent aurophilic bonding, i.e., a ligand-to-metal-metal charge transfer (LMMCT) transition [36][37][38][39][40][41][42][43][44][45][46] . Taking into account the allowed transitions with relatively large f values (f > 10 -2 ), the LMMCT transition was also the main electronic transition in the DT4 dimer.…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations
“…Thus, it can be concluded that 10-20-nm shift of the absorption wavelength was induced by dimer formation. The calculation results for the DT6 dimer, which have previously been reported, suggested that the electronic transitions in the excitation spectrum can be assigned to a transition from the ligand-based π-orbital to intermolecular non-covalent aurophilic bonding, i.e., a ligand-to-metal-metal charge transfer (LMMCT) transition [36][37][38][39][40][41][42][43][44][45][46] . Taking into account the allowed transitions with relatively large f values (f > 10 -2 ), the LMMCT transition was also the main electronic transition in the DT4 dimer.…”
Section: Resultsmentioning
confidence: 77%
“…Some Au(I) complexes exhibit AIE activity owing to an intermolecular interaction known as the aurophilic interaction 25,26 , in which a non-covalent Au-Au bond is formed between molecules. Because of this interaction, the luminescence of Au(I) complexes can be increased by aggregation in condensed phases [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] . We hypothesised that the introduction of multiple aurophilic interactions could further enhance the AIE activity of Au complexes [36][37][38][39][40][41][42][43][44][45][46] and enable us to visualise a crystallisation process clearly.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The Δ E orb stabilization from the inclusion rises to ~ − 50 kcal·mol −1 per Hg 0 atom. As a result, [M@Au 8 L 8 ] n+ can be viewed as Lewis acid species, such as [Hg 3 ( o ‐C 6 F 4 ) 3 ] and [Hg 5 (C(CF 3 ) 2 ) 5 ], and coinage metal trimers . The recent high‐yield synthesis of [PdAu 8 (PPh 3 ) 8 ] 2+ , reported by Tsukuda and coworkers, favors further experimental exploration to evaluate the incorporation of different relevant ions, such as Ag, Pb, Cd, and Zn, among others …”
Section: Resultsmentioning
confidence: 99%